Determinants of Non-Performing Loans in the Banking Sector of Ghana Between 1998 and 2013 - Adusei, Charles (Asian Development Policy Review, 2018)
This paper studied determinants of non-performing loans in Ghana, using historical time series annual data covering the period of 1998-2013. Using Seemingly Unrelated Regression model and Principal Component Analysis, the study found money supply, financial development and macroeconomics variables to be significant determinants of non-performing loans, except real income. The study recommends policies targeted at influencing non-performing loans.